Membentuk Generasi Qur’ani Melalui Kegiatan Baca Tulis Al Qur’an di MTs Nizhamiyah Ploso, Jombang - Hamzah; naashirudin, syahir; Maghribi, Hamdan (JOIES (Journal of Islamic Education Studies), 2025)
To face the swift flow of the times there needs to be a lot of effort in creating a generation of qur'ani through the activities of reading and writing the Qur'an one of them. The implementation of this research was carried out at MTs Nizhamiyah Ploso Jombang, using Qualitative research methods by obtaining data from sources of interviews of related parties and documentation. The purpose of the study was to determine the strategy of MTs Nizhamiyah Ploso in trying to create a generation of qur'ani through the activities of reading and writing the Qur'an. qur'ani generation is formed through a qur'an-based education In the implementation of reading and writing the Qur'an at MTs Nizhamiyah Ploso Jombang using the Tilawati Method and its implementation in the morning before the KBM starts, which has a noble goal of making students able to read the Qur'an, memorise and of course practice the teachings that are in it.